A Novel Spice: Pickled Pepper Powder and Some Quality Aspects - Cankaya Harika; Hayoglu Ibrahim; Turkoglu Huseyin (Polish Journal of Food and Nutrition Sciences, 2017)
An alternative pepper powder with better sensory quality was produced from some pickled pepper species. The peppers pickled via traditional and quick methods were dried at 65±1°C, ground and physical, chemical and sensory characteristics of the samples were compared to those of commonly consumed pepper powders (control). Capsicum species grown in Turkey including Chili, Kapia, Jordan, Biberiye, Frenk and etc. were used. The results are expected to contribute to the development of new products, to provide more alternatives for consumers in the market and to satisfy consumer expectations. Along with typical pickled aroma, hotness and colour, pickled pepper powders may be a valuable food additive especially for ready-to-eat and fast foods.